Design and Simulation of Electronic Load Controller with DC Dummy Load on Run Off River Type Micro Hydro Power Plant - Mardiyanto, Ignatius (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
Micro-hydro power plants are widely installed for electricity in rural areas with power quality is often an issue. In micro-hydro power plants with the Runoff River type, an electronic dummy load controller (ELC) is frequently used to control the frequency system. A dummy load can be either an Alternating Current (AC) or a Direct Current (DC). The principle of dummy load control is to make the output power always constant at the nominal power of the generator. The generator output power is steady when the consumer is changed, coupled with the dummy load. This research article is focused on a simulation of ELC settings with a DC Dummy Load so that the frequency and voltage on the generator side become relatively constant. This article also shows the effect of DC dummy load on generator power quality. The design of ELC Dummy Load DC is a 4-bit combination load with 16 different current values. The simulation running results illustrate the ability of the Dummy Load to maintain a voltage value of about 380 Volts and a frequency of 50 Hz. Therefore, it can be said that the generator output power quality due to the use of ELC Dummy Load DC control is not sufficient in the quality of the produced power. Total Demand Distortion (TDDi) and Total Harmonics Distortion (THDv) are up to 20%